Analysis of inpatient costs in patients with knee osteoarthritis treated by implantation of total condylar knee endoprosthesis - Pejčić, Ana; Radunović, Aleksandar; Vulović, Maja (Vojnosanitetski pregled, 2020)
Background/Aim. Total knee replacement is an elective and high cost surgical procedure which is performed more frequently as a result of increasing prevalence of knee osteo-arthritis. The aim of this study was to provide insight into the value and structure of inpatient costs associated with total knee replacement in Serbia. Methods. This study was conducted as an in-depth, bottom-up, retrospective, case series analysis of services consumption patterns and costs associated with inpatient treatment of patients with knee osteoarthritis by implantation of primary total condylar knee endoprosthesis from perspective of the national Republic Health Insurance Fund. We obtained data on 97 patients treated with primary unilateral or bilateral total knee replacement in 2014 at the Clinic for Orthopaedic Surgery and Traumatology of the Military Medical Academy in Belgrade, a tertiary health care university hospital. Results. Mean age of entire study sample was 67.89 years. Majority of patients (60 patients; 61.9%) had unilateral implantation of total condylar knee endoprosthesis. Bilateral implantation was performed in 37 (38.1%) patients. Mean total inpatient cost per patient for both unilateral and bilateral implantation of total condylar knee endoprosthesis was EUR 2,709.1, ranging from EUR 1,685.2 to EUR 5,356.6. Mean total inpatient cost per patient was EUR 2,093.8 for unilateral implantation and EUR 3,706.8 for bilateral implantation. Two major cost drivers were surgery specific material and surgery. Cost of implants was the highest single cost driver in all observed groups of patients. Conclusion. Our findings imply that inpatient costs associated with implantation of primary total condylar knee endoprosthesis are substantial. It seems that the most important cost drivers are surgery and surgery specific material, with implants being the highest single cost driver. Further research should be focused on analyzing factors that influence these costs in order to develop effective strategies which could contribute to substantial savings in the future.